Presentation of immunoregulatory sialoglycans on T cells is divergent between mice and humans - Fauzia N. Izzati; Hani Choksi; Paolo Giuliana; Diala Abd-Rabbo; Heidi Elsaesser; Aled Blundell; Vanessa Affe; Vinicius Kannen; Zeinab Jame-Chenarboo; Edward N. Schmidt; Meggie Kuypers; David B. Avila; et al. (Cell Reports)
Summary: Glycans are emerging as important regulators of T cell function but remain poorly characterized across the functionally distinct populations that exist in vivo. Here, we couple single-cell analysis technologies with soluble lectins and chemical probes to interrogate glycosylation patterns on major T cell populations across mouse and human tissues. Our analysis focused on terminal glycan epitopes with immunomodulatory functions, including sialoglycan ligands for Siglecs. We demonstrate that glycosylation patterns are diverse across the resting murine T cell repertoire and dynamically remodeled in response to stimulation. Surprisingly, we find that human T cell populations do not share the same glycoprofiles or glycan remodeling dynamics as their murine counterparts. We show that these differences can be explained by divergent regulation of glycan biosynthesis pathways between the species. These results highlight fundamental glycophysiological differences between mouse and human T cells and reveal features that are critical to consider for glycan-targeted therapies.